Case report: Ponatinib as a bridge to CAR-T cells and subsequent maintenance in a patient with relapsed/refractory Philadelphia-like acute lymphoblastic leukemia - Giglio, Fabio; Campodonico, Edoardo; Lorentino, Francesca; Noviello, Maddalena; Xue, Elisabetta; Greco, Raffaella; Lazzari, Lorenzo; Bruno, Alessandro; Lupo Stanghellini, Maria Teresa; Carrabba, Matteo Giovanni; La Starza, Roberta; Casucci, Monica; et al. (Frontiers in Oncology, 2023)
Philadelphia (Ph)-like acute lymphoblastic leukemia (ALL) constitutes a heterogeneous subset of ALL with a uniformly unfavorable prognosis. The identification of mutations amenable to treatment with tyrosine kinase-inhibitors (TKIs) represents a promising field of investigation. We report the case of a young patient affected by relapsed/refractory Ph-like ALL treated with chimeric antigen receptor T (CAR-T) cells after successful bridging with compassionate-use ponatinib and low-dose prednisone. We restarted low-dose ponatinib maintenance three months later. Twenty months later, measurable residual disease negativity and B-cell aplasia persist. To the best of our knowledge, this is the first case reporting the use of ponatinib in Ph-like ALL as a bridge to and maintenance after CAR-T cell therapy.